Zero corporate income tax in Moldova : tax competition and its implications for Eastern Europe - Piatkowski, Marcin; Jarmuzek, Mariusz (IMF working paper ;, 2008)
Global economic integration intensified tax competition and raised concerns about the resulting "race to the bottom", which could undermine public investment and social spending. The aim of this paper is to test predictions that (i) there is interdependence in CIT rate setting in Eastern Europe and that (ii) the recent CIT cut in Moldova may intensify tax competition in the region. It finds that there is indeed evidence that during 1995-2006 countries in Eastern Europe strategically responded to changes in CIT rates in the region and that Moldovan zero CIT is likely to encourage further cuts in CIT. The paper also discusses implications of tax competition for Eastern Europe and finds that FDI flows will not be much affected, tax revenues are likely to decline, the shift in the composition in tax revenue may increase economic efficiency, but decrease equity. Tax coordination, while difficult politically, could help stem further decline in corporate taxation, but any gains might be modest and not certain to exceed the costs of tax coordination. Without tax coordination, however, it is unclear what exactly could stop corporate taxes from falling further